دراسة فاعلية تقنية التيرمكس وتأثيرها على الخواص الميكانيكية لقضبان حديد التسليح المنتجة في معمل آسكو - هترة, علي; سلامه, أحمد; جابر, أيمن (Latakia University Journal -Engineering Sciences Series, 2018)
تهدف الدراسة الى تحسين الخواص الميكانيكية ( اجهاد الخضوع و مقاومة الشد ) لقضبان التسليح عن طريق استخدام تقنية التيرمكس بعد اضافتها الى خط الانتاج.استخدام قضبان التسليح بنوعية عالية و متنوعة من مختلف انواع البيليت يؤدي الى خفض كلف الانتاج مما ينعكس على تخفيض كلف البناء ايضا.استخدام تقنية التيرمكس لمعالجة القضبان، يمنح المنتج امكانية التحكم بالخواص الميكانيكية عن طريق تغيير بعض العوامل الأساسية في عملية الإنتاج مثل ( سرعة القضبان اثناء عملية الانتاج – كمية تدفق الماء– و ضغط الماء) في التيرمكس. تركزت الدراسة على العوامل انفة الذكر والتيرمكس و مكوناته في المرحلة النهائية من عملية الدرفلة,و تأثيره على خواص الشد لقضبان فولاذ التسليح.This study is on improvement the mechanical properties (yield strength – stress) of deformed steel bars by using design of thermex for robust process design.Producing deformed steel bars in high quality and long variation of mechanical properties from deferent kinds of billets it caused to degree the cost of production and in other side it will degree the cost of construction works.By using thermex in production of deformed steel bars give us the possibility to control the mechanical properties by changing some factors in production process like rolling speed - water pressure - water flow in thermex strippers The research has concentrate on aforementioned production factor’s and Thermex elements in finishing area of rolling process.